Airport energy conservation and runway configuration - Li Xiong; Chen Xiaoqing (E3S Web of Conferences, 2024)
Efficient ground operation of aircraft directly impacts airport's courses of energy conservation and green operation. Typical runway configurations used in large airport were classified and analyzed. Combining with flight ground operation, 2 methods of comparison and selection of carbon emission were proposed, which were based on taxiing distance and simulation respectively. In addition, above 2 methods were applied in large-sized airport runways configuration selection and taxiways optimization. Application results show that the method based on taxiing distance suits for rough estimation in the early stage of airport planning, the method based on simulation considering both ground taxiing and delay time suits for a more detailed study on airport planning.